2017
DOI: 10.1172/jci89857
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer kinase inhibitors impair intracellular viral trafficking and exert broad-spectrum antiviral effects

Abstract: Global health is threatened by emerging viral infections, which largely lack effective vaccines or therapies. Targeting host pathways that are exploited by multiple viruses could offer broad-spectrum solutions. We previously reported that AAK1 and GAK, kinase regulators of the host adaptor proteins AP1 and AP2, are essential for hepatitis C virus (HCV) infection, but the underlying mechanism and relevance to other viruses or in vivo infections remained unknown. Here, we have discovered that AP1 and AP2 cotraff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
321
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(335 citation statements)
references
References 68 publications
12
321
1
1
Order By: Relevance
“…Our results thus confirm and extend the published finding by demonstrating that sunitinib and anti-TNF acted synergistically to improve survival without affecting tissue viral burden. This is consistent with studies showing that sunitinib or anti-TNF treatment alone had no effects on viremia (Bekerman et al, 2017; Phanthanawiboon et al, 2016). In addition to the known effects of sunitinib on angiogenesis and vascular permeability (Hofmann et al, 2002; Inyoo et al, 2017; Marzola et al, 2005), TNF blockade alone has been shown to decrease vascular leakage in DENV-infected mice (Ng et al, 2014; Watanabe et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Our results thus confirm and extend the published finding by demonstrating that sunitinib and anti-TNF acted synergistically to improve survival without affecting tissue viral burden. This is consistent with studies showing that sunitinib or anti-TNF treatment alone had no effects on viremia (Bekerman et al, 2017; Phanthanawiboon et al, 2016). In addition to the known effects of sunitinib on angiogenesis and vascular permeability (Hofmann et al, 2002; Inyoo et al, 2017; Marzola et al, 2005), TNF blockade alone has been shown to decrease vascular leakage in DENV-infected mice (Ng et al, 2014; Watanabe et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Anti-malaria quinolones (chloroquine and hydroxychloroquine) inhibit acidification of endosomes, which is an essential process for uncoating of ssRNA viruses (Al-Bari, 2017). Anticancer kinase inhibitors dasatinib, imatinib, gefitinib, nilotinib, erlotinib and sunitinib impair intracellular viral trafficking and exert BSA effects (Bekerman et al, 2017;Schor and Einav, 2018). The anti-Duchenne muscular dystrophy agent, alisporivir, targets cellular cyclophilin and inhibits the folding of HCV, HIV, MERS-and SARS-CoV proteins, and, therefore, prevents formation of infectious virus particles (Boldescu et al, 2017;de Wilde et al, 2017;Soriano et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…While GAK‐dependent phosphorylation of AP2 is important for its endocytic activity, GAK′s phosphorylation of AP1 is implicated in trans‐Golgi network (TGN)‐to‐lysosome trafficking. This phosphorylation of APs enhances their binding to cargo proteins and helps the recruitment of clathrin to the membrane to form a clathrin‐coated vesicle (CCV) . In analogy to auxilin I, GAK contains a C‐terminal J‐domain that acts as a co‐chaperone with the heat shock cognate 71 kDa protein (HSC70) to uncoat CCVs in order to recycle clathrin back to the cell surface .…”
Section: Introductionmentioning
confidence: 99%